Global citizenship education and the crises of multiculturalism comparative perspectives - Tarozzi, Massimiliano (London Bloomsbury Academic, 2016)
The notion of global citizenship education (GCE) has emerged in the international education discourse in the context of the United Nations Education First Initiative that cites developing global citizens as one of its goals. In this book, the authors argue that GCE offers a new educational perspective for making sense of the existing dilemmas of multiculturalism and national citizenship deficits in diverse societies, taking into account equality, human rights and social justice. The authors explore how teaching and research may be implemented relating to the notion of global citizenship and discuss the intersections between the ideology of GCE and multiculturalism. They address the three main topics which affect education in multicultural societies and in a globalized world, and which represent unsolved dilemmas: the issue of diversity in relation to creating citizens, the issue of equality and social justice in democratic societies, and the tension between the global and the local in a globalized world. Through a comparative study of the two prevailing approaches - intercultural education within the European Union and multicultural education in the United States - the authors seek what can be learned from each model. Global Citizenship Education and the Crises of Multiculturalism offers not only a unifying theoretical framework but also a set of policy recommendations aiming to link the two approaches
Includes bibliographical references (pages [177]-203) and index.
Keywords: Education and globalization